Recent trends and advances in microbe-based drug delivery systems - Shende, Pravin (Daru, 2019)
Since more than a decade, pharmaceutical researchers endeavor to develop an effective, safe and target-specific drug delivery system to potentiate the therapeutic actions and reduce the side effects. The conventional drug delivery systems (DDSs) show the improvement in the lifestyle of the patients suffering from non-communicable diseases, autoimmune diseases but sometimes, drug resistance developed during the treatment is a major concern for clinicians to find an alternative and more advanced transport systems. Advancements in drug delivery facilitate the development of active carrier for targeted action with improved pharmacokinetic behavior. This review article focuses on microbe-based drug delivery systems to provide safe, non-toxic, site-specific targeted action with lesser side effects. Pharmaceutical researchers play a vital part in microbe-based drug delivery systems as a therapeutic agent and carrier. The properties of microorganisms like self-propulsion, in-situ production of therapeutics, penetration into the tumor cells, increase in immunity, etc. are of interest for development of highly effective delivery carrier. Lactococcus lactis is therapeutically helpful in Inflammatory Bowel Disease (IBD) and is under investigation of phase I clinical trial. Moreover, bacteria, anti-cancer oncolytic viruses, viral vectors (gene therapy) and viral immunotherapy are the attractive areas of biotechnological research. Virus acts as a distinctive candidate for imaging of tumor and accumulation of active in tumor. [Figure: see text]